Learn Welding Techniques to Improve Work Skills in Vocational School Students - Eril Setiawan; Rendi Salam; Adi Adi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Welding training is a learning activity about the science and practice of welding, so that the trainees know the correct welding methods and can practice them. It is hoped that this training activity can become one of the competency provisions for the training participants, in this case the youth of the Pondok Benda sub-district, South Tangerang. In order for this activity to run smoothly, a scientific method was established, namely a theoretical explanation of welding and practice. The participants in this activity were teenagers who were members of the Pondok Benda sub-district, South Tangerang youth organization, which totaled 45 people. The activity was carried out at the community hall RW 014 Pondok Benda, South Tangerang, on Saturday, July 30 2022. This activity went smoothly and the participants were very enthusiastic. It was evident that many questions were asked, the participants' responses were very enthusiastic, and the participants were very enthusiastic about participating in the welding practice. This activity was welcomed positively, because according to one of the training participants, this activity can form welding skills that are useful for the world of work.